New record of predatory mite (Prostigmata: Ereynetidae) with some cheyletid mites (Acari: Cheyletidae) from garlic agrosystems in Turkey - Çobanoğlu, Sultan; Cilbircioğlu, Cihan; Zabludovskaya, Svetlana A. (Informa UK Limited, 2019)
ABSTRACTEreynetes (Ereynetes) septentrionalis (Berlese) (Ereynetidae) samples were collected from storage spaces and garlic growing areas in Kastamonu─Turkey. The family Ereynetidae and Ereynetes a...